Respiratory Mechanics in a Cohort of Critically Ill Subjects With COVID-19 Infection. - Longino, August; Riveros, Toni; Risa, Erik; Hebert, Chris; Krieger, Joshua; Coppess, Steven; McGuire, Flynn; Bhatraju, Pavan K.; Town, James; Johnson, Nicholas J. (Respiratory Care, 2021)
BACKGROUND: Patients with coronavirus disease 2019 (COVID-19) often develop acute hypoxemic respiratory failure and receive invasive mechanical ventilation. Much remains unknown about their respiratory mechanics, including the trajectories of pulmonary compliance and PaO2/FIO2, the prognostic value of these parameters, and the effects of prone positioning. We described respiratory mechanics among subjects with COVID-19 who were intubated during the first month of hospitalization. METHODS: We included patients with COVID-19 who were mechanically ventilated between February and May 2020. Daily values of pulmonary compliance, PaO2, FIO2, and the use of prone positioning were abstracted from electronic medical records. The trends were analyzed separately over days 1-10 and days 1-35 of intubation, stratified by prone positioning use, survival, and initial PaO2/FIO2. RESULTS: Among 49 subjects on mechanical ventilation day 1, the mean compliance was 41 mL/cm H2O, decreasing to 25 mL/cm H2O by day 14, the median duration of mechanical ventilation. In contrast, the PaO2/FIO2 on day 1 was similar to day 14. The overall mean compliance was greater among the non-survivors versus the survivors (27 mL/cm H2O vs 24 mL/cm H2O; P = .005), whereas PaO2/FIO2 was higher among the survivors versus the non-survivors over days 1-10 (159 mm Hg vs 138 mm Hg; P = .002) and days 1-35 (175 mm Hg vs 153 mm Hg; P < .001). The subjects who underwent early prone positioning had lower compliance during days 1-10 (27 mL/cm H2O vs 33 mL/cm H2O; P < .001) and lower PaO2/FIO2 values over days 1-10 (139.9 mm Hg vs 167.4 mm Hg; P < .001) versus those who did not undergo prone positioning. After day 21 of hospitalization, the average compliance of the subjects who had early prone positioning surpassed that of the subjects who did not have prone positioning. CONCLUSIONS: Respiratory mechanics of the subjects with COVID-19 who were on mechanical ventilation were characterized by persistently low respiratory system compliance and PaO2/FIO2, similar to ARDS due to other etiologies. The PaO2/FIO2 was more tightly associated with mortality than with compliance.